Breeding biology of Bengal eyed turtle Morenia petersi (Anderson 1879) in Bangladesh (Bangladesh Journal of Zoology, 2015)
This study was conducted to determine the breeding season, gonad development, egg laying period, clutch size and other biological aspects of Bengal Eyed Turtle, Morenia petersi of Bangladesh. The egg-laying period was found between November and February. The nesting sites were elevated fallow lands in secluded areas. The female turtle laid all the mature eggs at a time for each clutch at night. A gravid female turtle laid two clutches of eggs in each breeding season and the mean clutch size was 9.7 ± 1.5 eggs and mean weight of each egg was 8.9 ± 1.3 g. The eggs are elongated in shape and whitish in colour. The mean incubation period was 119 ± 30 days. The incubation period of first clutch was the longer than the second clutch. The hatchlings emerged out between April and May. Hatchery success was found 56.8%. The percentage of weight gain and specific growth rate (SGR) by weight of hatchlings in the first year was greater than second and third year. Present investigation was made to explore the possibility to raise turtle farming in captive condition.Bangladesh J. Zool. 42(2): 169-181, 2014